Submandibular and sublingual salivary gland involvement in adenoid cystic carcinoma - Poonam Ramnath Sawant; Manjeeta Mahesh Sinai Dhume; Anita Spadigam; Anita Dhupar (University of São Paulo, 2024)
Adenoid cystic carcinoma (AdCC) is a malignant salivary gland neoplasm that presents as an indolent but aggressive neoplasm. AdCC histogenesis is linked to the intercalated ducts of the salivary glands, equally affecting the major and minor glands. AdCC is associated with distant metastasis, most commonly to the lungs, and a high recurrence rate. AdCC accounts for 4.2% of all tumors. About 55% of all reported cases affect the submandibular gland, and around 50% of AdCC cases occur in the minor salivary glands. The present review describes a case of AdCC which presented a single nodular swelling on the right side involving the floor of the mouth. It also consolidates the histopathological profile of a case of AdCC with all the relevant histopathological features.